Exploring gender-based disparities in finalist technical-tactical actions: a study of amateur and professional padel players - Fernández de Ossó, A. I.; Conde-Ripoll, R.; Muñoz, D.; Escudero-Tena, A. (Perceptual and Motor Skills, 2025)
Our aim in this study was to analyze gender differences across amateur and professional padel players related to the last shot of each rally. We analyzed a total of 180 games per category (professional and amateur), with 90 games for each gender. We performed descriptive and inferential analyses, including the Chi-square (?2) statistical test, the Cramer`s V coefficient (Vc), subsequent Z-tests and corrected standard residuals (CSR). Results revealed that male amateurs produced more winners than female amateurs (CSR = 3.2). Conversely, male professionals exhibited more forced errors (CSR = 3.0) than female professionals, while female professionals committed more unforced errors (CSR = 3.8). In addition, there was a significant relationship between the type of the last shot played and player gender among amateurs, particularly when the last shot resulted in a winner (p < .001) or an unforced error (p = .011). Similarly, among professionals, there was a significant relationship between gender and last shot play when the last shot was a forced error (p = .009). Likewise, there was a relationship between the court zone and gender in amateur padel, when the last shot was an unforced error (p = .002) and among professionals, when the last shot was a winner (p = .001). In conclusion, the type of technical-tactical action, its effectiveness, and the area of the court were influenced by the players` sex in both amateur and professional padel.